Tuning the selective sensing properties of transition metal dichalcogenides (MoX2: X= Se, Te) toward sulfurrich gases. (December 2022) - Panigrahi, P.; Pal, Y.; Raval, D.; Gupta, S.K.; Gajjar, P.N.; Bae, H.; Lee, H.; Mark, S.; Ahuja, R.; Pandey, R.; Hussain, T.
Abstract: There is an urgent need for an efficient sensor to mitigate the effects of toxic pollutants possessing severe impacts on humans and the environment. Motivated by this, we investigated the selected transition metal dichalcogenides (MoX2 : X = Se, Te) monolayers toward the toxic sulfur-containing gases, such as H2 S and SO2 . We employed density functional theory simulations in combination with nonequilibrium Green's function formalism to study the optimized geometries, binding strength, electronic structures, charge transfer mechanism, and transport (current–voltage) characteristics of MoX2 with and without H2 S and SO2 . Weak binding energies (<-0.30 eV) of H2 S/SO2 on pristine MoX2 were enhanced by selectively substituting the latter with elements like As, Ge, and Sb at lower doping concentrations of around 2%. We find that the doped MoX2 strongly adsorbs H2 S/SO2 yielding significant changes in their electronic properties, which were the fundamentals for the efficient sensing mechanism and were studied through the density of states and work function calculations. For the practical sensing applications, we considered the statistical thermodynamic analysis to investigate the sensing properties of pristine and doped MoX2 monolayers under varied conditions of the temperatures and pressures. We are confident that our findings would pave the way for synthesizing sensitive and selective transition metal dichalcogenides-based nanosensor toward H2 S/SO2 . Graphical abstract: Image 1 Highlights: Pure and defected MoSe2, and MoTe2 as efficient nanosensors toward H2 S, and SO2 . DFT, non-equilibrium Green's function, and thermodynamic analysis are used. Gas adsorption abilities under the practical conditions of temperature and pressures. As–MoSe2, Ge-MoSe2 and Sb–MoTe2 have shown a superior and selective sensing performance. Selective H2 S/SO2 sensing are verified through current-voltage (I–V) characteristics.